Analysis of motivational factors that influence in the use of Facebook and the satisfaction of students of the National Agrarian University La Molina, Lima-Peru - Ferrando Perea, Ampelio (2022)
This study was carried out with the objective of identifying the reasons associated with the use of Facebook in undergraduate students of the Universidad Nacional Agraria La Molina. The research has followed the non-experimental descriptive guideline and was carried out through a survey applied to 372 undergraduate students from twelve professional careers at the La Molina National Agrarian University. Six motivational factors were analyzed: self-expression, company, virtual community, coolness, entertainment, and relationship maintenance. The study concluded that the most influential motivational factors in the satisfaction of the use of Facebook in undergraduate students of the Universidad Nacional Agraria La Molina are virtual community, entertainment, and self-expression; and the least influential, company, relationship maintenance, and coolness.